2008
DOI: 10.1002/cncr.23683
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of transketolase‐like‐1 in papillary thyroid carcinomas smaller than 1.5 cm in diameter is associated with lymph‐node metastases

Abstract: In this study, the structure–property relationships for a series of statistical 2‐nonyl‐2‐oxazoline (NonOx) and 2‐phenyl‐2‐oxazoline (PhOx) copolymers were investigated for the first time. The copolymerization kinetics were studied and the reactivity ratios were calculated to be rNonOx = 7.1 ± 1.4 and rPhOx = 0.02 ± 0.1 revealing the formation of gradient copolymers. The synthesis of a systematical series of NonOx–PhOx copolymers is described, whereby the amount of NonOx was increased in steps of 10 mol %. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…According to the results of several clinical studies, overexpression of TKTL-1 is associated with a poor prognosis (2)(3)(4)(5). Experimental data have been published (1,(6)(7)(8) which apparently confirm the pathophysiological basis of TKTL-1-associated aggressiveness observed in clinical studies.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…According to the results of several clinical studies, overexpression of TKTL-1 is associated with a poor prognosis (2)(3)(4)(5). Experimental data have been published (1,(6)(7)(8) which apparently confirm the pathophysiological basis of TKTL-1-associated aggressiveness observed in clinical studies.…”
Section: Introductionsupporting
confidence: 59%
“…Omissions in this communication, however, prevent an objective evaluation of this interpretation. Nevertheless, several studies using the antibody clone JFC12T10 in other tumor entities also reported an unfavorable prognostic significance of increased expression of TKTL-1 (2,4,5). In the present study, the importance of TKTL-1 for malignant tumor cells has been evaluated on the basis of our own experimental data.…”
Section: Introductionmentioning
confidence: 93%
“…This is in accordance with a significant overexpression of TKTL1 in several different tumors like nasopharyngeal [16] , pulmonary [17] , thyroid papillary [18,19] , gastric [20] , ovarian [21,22] , cervical [23] and metastasizing renal cell carcinoma [11] . In general, increased TKTL1 expression correlates with poor patient outcome and tumor progression [20,[23][24][25] .…”
Section: Introductionmentioning
confidence: 48%
“…Via genome duplication and exon skipping, higher vertebrates acquired transketolase-like 1 (TKTL1), which compared to TKT protein lacks 38 amino acid residues [8, 9]. TKTL1 is upregulated in various cancer cells and tissues [4, 5, 1013], and TKTL1 overexpression in cancer patients is correlated with malignancy, invasiveness, therapeutic resistance and poor prognosis [11, 1416]. TKTL1 is required for rapid growth and viability of tumor cells [17], and protects against apoptosis induced by growth factor withdrawal [18], oxidative stress [1719], cytotoxic therapy or targeted therapies [16, 20], while TKTL1 silencing hinders cancer cell proliferation [17, 21].…”
Section: Introductionmentioning
confidence: 99%